Hardware-Accelerated Non-Contact System for Sleep Disorder Monitoring and Analysis - Mangali Sravanthi; Sravan Kumar Gunturi; Mangali Chinna Chinnaiah; G. Divya Vani; Mudasar Basha; Narambhatla Janardhan; Dodde Hari Krishna; Sanjay Dubey (Sensors)
This study analyzes human sleep disorders using non-contact approaches. The proposed approach analyzes periodic limb movement disorder (PLMD) under sleep conditions. This was conceptualized as data capture using a non-contact approach with ultrasonic sensors. The model was designed to estimate PLMD and classify it using real-time sleep data and a machine learning-based random forest classifier. Hardware schemes play a vital role in capturing sleep data in real time using ultrasonic sensors. A field-programmable gate array (FPGA)-based accelerator for a random forest classifier was designed to analyze PLMD. This is a novel approach that aids subjects in taking further medications. Verilog HDL was used for PLMD estimation using a Xilinx Vivado 2021.1 simulation and synthesis. The proposed method was validated using a Xilinx Zynq-7000 Zed board XC7Z020-CLG484.